Strangers and friends meet in virtual reality: the influence of prior acquaintance in social VR scenarios - Tütüncü, Esen K.; Oliva, Ramon; Slater, Mel (Frontiers in Virtual Reality, 2025)
IntroductionVirtual reality (VR) is typically considered a single-user experience. However, since the early 1990s, systems have been developed and studied that allow multiple people to simultaneously inhabit the same virtual space, with each person represented by a virtual body that responds to their movements in real time through head and body tracking. Corresponding to this technical capability the concepts of copresence (the sensation of being with others) and social presence (the psychological correlates of being and interacting with others) have been studied. One important contributor to the outcome of a virtual meeting may be the prior relationship between the individuals. Just as in real-world meetings, the dynamics of social interactions may differ depending on whether the participants are friends or strangers.MethodsIn this paper, we report on a study with 50 participants, each in one of 16 groups of 3–4 people and a moderator, where eight of the groups consisted of friends and the other groups consisted of strangers. Each participant had a virtual body that resembled themselves. They engaged in a moderator-led discussion lasting approximately 17 min. We collected data through questionnaires measuring presence and copresence, and carried out sentiment analysis of participant post-experience essays, analysis of speaking time and turn-taking, and social network analysis.ResultsWe found that groups of friends reported higher copresence, showed more positive sentiment, and engaged more frequently in behaviors such as dyadic turn-taking than the groups of strangers.DiscussionWhen designing and deploying immersive social encounters, prior relationships between participants should be considered where possible since these can significantly alter the dynamics of social interaction.